(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
A safety and immunogenicity field trial to evaluate a live recombinant human adenovirus (serotype 5)-rabies glycoprotein vaccine (ONRAB®) in raccoons and skunks was conducted in the U.S. in 2011. Approximately 80,000 Ultralite baits (Artemis Technologies, Guelph, ON, CAN) were distributed at 75 baits/km2 along 750m flight lines in 4, 127 km2 study areas in southeastern West Virginia, U.S. The bait was composed of a small blister pack that contained the ONRAB® vaccine with a waxy coating matrix of attractants impregnated with tetracycline biomarker, and camouflaged by a green dye. No phone calls from human or pet bait contacts were reported through a toll-free phone number provided on each bait. Low human population density may largely account for no reported bait contacts. No tissue abnormalities were observed in captive cottontail rabbits, opossums, fox squirrels, eastern wild turkeys, and woodrats at a 10x ONRAB® dose, and field histopathology results should be available in December 2012. Rabies virus neutralizing antibody (RVNA) was higher among raccoons (P<0.05) in post-ONRAB® samples (49.4%, n=296) than in naïve pre-ORV samples (9.6%, n=395). Biomarker was higher (P<0.05), among post-ONRAB® raccoons sampled, an indication of vaccine-induced RVNA’s. The 49.4% RVNA population level in raccoons is the highest observed in the U.S. for a first time oral rabies vaccine distribution event. Skunk sample size was inadequate to assess ONRAB® effects. Field trial results warranted replication and expansion in 2012 to assess raccoon population immunity from a second ONRAB® trial in four more states, including Ohio urbansuburban habitats. These collaborative trials, which will continue to bring together multiple disciplines from county, state, federal and international jurisdictions in the spirit of One Health, should provide a basis to determine if ONRAB® is suited to achieve raccoon rabies management goals.